At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

If [tex]JM = 5x - 8[/tex] and [tex]LM = 2x - 6[/tex], which expression represents [tex]JL[/tex]?

A. [tex]3x - 2[/tex]
B. [tex]3x - 14[/tex]
C. [tex]7x - 2[/tex]
D. [tex]7x - 14[/tex]


Sagot :

To determine the expression for [tex]\(JL\)[/tex], we need to add the given expressions for [tex]\(JM\)[/tex] and [tex]\(LM\)[/tex].

1. Given:
[tex]\[ JM = 5x - 8 \][/tex]
[tex]\[ LM = 2x - 6 \][/tex]

2. We seek the expression for [tex]\(JL\)[/tex]:
[tex]\[ JL = JM + LM \][/tex]

3. Substitute the expressions for [tex]\(JM\)[/tex] and [tex]\(LM\)[/tex]:
[tex]\[ JL = (5x - 8) + (2x - 6) \][/tex]

4. Combine like terms:
- Combine the [tex]\(x\)[/tex] terms:
[tex]\[ 5x + 2x = 7x \][/tex]
- Combine the constant terms:
[tex]\[ -8 - 6 = -14 \][/tex]

5. Therefore, the resulting expression is:
[tex]\[ JL = 7x - 14 \][/tex]

So, the correct answer is [tex]\(\boxed{7x - 14}\)[/tex].